Antioxidant, starch-digesting enzymes inhibitory, and pasting properties of elite yellow-fleshed cassava genotypes - Kareem, Babajide; Irondi, Emmanuel Anyachukwu; Alamu, Emmanuel Oladeji; Ajani, Emmanuel Oladipo; Abass, Adebayo; Parkes, Elizabeth; Maziya-Dixon, Busie (Frontiers in Sustainable Food Systems, 2023)
Cassava root has been improved from its traditional starchy status to a rich source of bioactive compounds, especially carotenoids, with some health benefits, through biofortification. This study contains the bioactive constituents (carotenoids, tannins, total phenolics and flavonoids), antioxidant, and starch-digesting enzymes (α-amylase and α-glucosidase) inhibitory and pasting properties of flours of 18 elite yellow-fleshed cassava genotypes were evaluated. Flours of the 18 elite yellow-fleshed cassava genotypes grown at the International Institute of Tropical Agriculture were analysed using standard laboratory methods. Generally, the concentrations of the bioactive constituents (9-cis-β-carotene, 13-cis-β-carotene, all trans-β-carotene, total β-carotene, total carotenoids, tannins, total phenolics, and total flavonoids) of the different cassava genotypes varied. There was also a significant difference in the antioxidant activity of the different cassava genotypes. However, the starch-hydrolysing enzymes (α-amylase and α-glucosidase) inhibitory and the pasting properties of the different genotypes were generally comparable. Total carotenoids content significantly correlated with the DPPH• SC50 (r = -0.495), while total phenolics content correlated with ABTS•+ (r = 0.839) and DPPH• SC50 (r = -0.870). Also, tannin content significantly correlated with ABTS•+ (r = 0.553), while total flavonoid content was significantly correlated with α-amylase IC50 (r = -0.532). These findings suggest the potential of flours of the 18 elite yellow-fleshed cassava genotypes to serve as important dietary sources of antioxidants and starch-hydrolysing enzyme inhibitors, which may be beneficial in oxidative stress and postprandial hyperglycaemic conditions.